Case Report: Cranial intradural chordoma following extradural spinal chordoma - Sarı, Ramazan; Akçakaya, Mehmet Osman; Özyılmaz, Kadir; Temel, Yasin; Elmacı, Ilhan (Frontiers in Surgery, 2025)
Chordomas are rare, locally invasive, and slow-growing neoplasms that originate from remnants of the primitive notochord. They account for approximately 1% of all intracranial tumors and are typically found in the sacrococcygeal region or at the skull base. Purely intradural intracranial chordomas are exceptionally rare, with only 67 cases documented to date, to the best of our knowledge. These tumors are generally situated near the midline. We present the case of a 67-year-old male who developed hemiparesis and hemihypoesthesia 6 years after undergoing surgery for a classical spinal chordoma that was purely extradural. Magnetic resonance imaging revealed a mass in the frontoparietal area, initially suggestive of an intraaxial tumor. However, intraoperative findings indicated that the lesion was extraaxial, and histopathological evaluation confirmed it as an intradural chordoma. To our knowledge, this is the first reported case of a chordoma within the brain parenchyma and away from the midline.